PENGALIHAN HAK TANAH ULAYAT PADA BANDAR UDARA SENTANI DI JAYAPURA PAPUA - , PAULA MUSTIKA DEWI HEREWILLA; , Ir. Suryanto, MSP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sentani's Airport in Jayapura, has a legal status based on Besluit is de gouverneur's van Nederlands Nieuw's van Guinea Number 63 Years 1961, however its existences not recognized by local customary community. This research aims (1) to document the handover process of the right, (2) to document the conflicts, (3) Pattern of Conflict resolution, (4) factors contributed to conflict and (5) factors contributed to conflict resolution. In the land rights transfer, there are differences in perceptions between the government and local customary community, such as differences the related state of land, the legal ownership, and the amount of compensation for such lands. In addition, the existence of third parties who claim ownership of airport land, so that the government faces other charges again. Efforts performed by the government to overcome the conflict is through judicial to obtain legal certainty, to discussion with local customary community and formed the committee as a facilitator to give the compensation for local customary community. Apart form the loss of money, local customary community also covet the compensation, in another form that can be improve the lives of local customary community, whose existence can be exploited forever, such as education, employment and others. to respond it, the government in this case the sentani airport can make CSR (corporate social responsibility) or corporate social responsibility as it has done in many other airports in Indonesia.